A Comprehensive Review of Ergonomics and Human Factors Engineering for Enhancing Comfort and Efficiency in Transport Systems - Petruța Blaga; Bianca-Mihaela Cășeriu; Bogdan Bucur; Cristina Veres (Systems)
This research provides an integrated perspective on the application of ergonomics and human factors engineering (HFE) to enhance comfort and efficiency in military transport systems (MTS) and civilian transport systems (CTS), identified as imperative research needs. Comfort has become the definition of vehicle quality in CTS, while in MTS, comfort directly influences crew performance in operational environments, and protecting their health is essential. The study emphasizes the importance of adopting an integrative and scientifically grounded approach that eliminates systematic errors to meet user needs and ensure optimal vehicle performance in diverse operational settings. It further highlights how applying ergonomic principles optimizes human–machine interactions, improving user comfort and safety while providing a basis for future innovations in artificial intelligence and adaptive ergonomics. This study introduces a novel hybrid methodology combining bibliometric analysis and case studies to provide fresh insights into the application of ergonomics and human factors engineering, bridging gaps between civilian and military transport systems. This approach aims to promote efficiency, comfort, and performance in operational environments. The results confirm the research hypotheses, demonstrating that ergonomic principles and human factors engineering (HFE) can significantly enhance the comfort, safety, and performance of vehicle users in both civilian and military contexts.